The Development of a Canadian Integrated Ocean Observing System (CIOOS) - Stewart, Andrew; deYoung, Brad; Smit, Mike; Donaldson, Karen; Reedman, Alexa; Bastien, Andréane; Brunsting, Ray; Carter, Bill; Covey, Brad; Kelly, Richard; Peterson, Eric; Pirenne, Benoît; et al. (Frontiers in Marine Science, 2019)
Ocean observation is fundamental to Canada’s ocean science community. The federal government, academia, small businesses, not-for-profit organizations, and other research partners, collect and synthesize physical, chemical and biological observations for research purposes, to model ocean changes, to support resource management decision-making, and to establish baseline data for long-term monitoring. Aside from building comprehensive ocean observatories (Fisheries and Oceans Canada (DFO) et al. 2010), there is no easy mechanism to integrate the large amounts of data from the various sources or to explore interrelationships among variables, and no coordination and collaboration mechanism for the ocean community as a whole to generate an efficient system (Ocean Science and Technology Partnership (OSTP), for Fisheries and Oceans Canada (DFO) 2011). Consequently, we observe fragmented and isolated data that is only discoverable by a limited range of end users. Canada’s ocean science community (Wallace et al. 2014), led and supported by Fisheries and Oceans Canada (DFO), is developing a Canadian Integrated Ocean Observation System (CIOOS) that brings together and leverages existing Canadian and international ocean observation data into a federated data system. This system (Wilson et al. 2016) will improve coordination and collaboration among diverse data producers, improve access to information for decision making, and enable discovery and access to data to support a wide variety of applied and theoretical research efforts to better understand, monitor, and manage activities in Canada’s oceans. Canada is implementing a CIOOS test-phase, which will eventually lead to the development of a robust and integrated observing system, improving connections between end users and providers of ocean observations. The improved coordination of regional and national efforts within CIOOS will contribute to global ocean observing, maximizing the overall benefit of integrated observing.